Kinetic and Equilibrium Studies of Congo Red Adsorption on Adsorbent fromBambara Groundnut Hulls - Akinola, L.K.; Ibrahim, A.; Chadi, A.S. (Al-Hikmah Journal of Pure and Applied Sciences (AJPAS), 2016)
Kinetics and equilibrium isotherms of Congo red adsorption on adsorbent derived from Bambara groundnut (Vignasubterranea (L) Verdc.) hulls were investigated in a series of batch experiments. Using a one-factor-at-a-time(OFAT) approach, optimum removal efficiency of Congo red by the adsorbent occurred at pH of 6.0 at loweradsorbent dosage, attaining a peak value of 72.79% after 4 hours of agitating time. Findings also revealed that,among the kinetic and isotherm models tested, the experimental data fitted best to pseudo-second order model ( =0.957) and Freundlich adsorption isotherm ( = 0.981). This suggests that Congo red adsorption on Bambaragroundnut hulls involves chemisorption and the process is indicative of cooperative adsorption. The studydemonstrates that Bambara groundnut hulls can serve as an alternative low-cost adsorbent for removing Congo redfrom industrial wastewater